Beiträge zur Insekten-Fauna der DDR: Hymenoptera - Sphecidae. - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1970)
Among the 202 species of the family Sphecidae identified in the GDR there are 25 species that have not been reported in the last three decades. 19 species were noted as new. The occurrence of 27 species is probable, but as yet no specimens have been definitely determined in this territory. Thus the total can be expected to reach 229 species. This paper presents keys to these species drawn up according to modern taxonomical views. After evaluating the publications and revising all larger collections the author compiled data about the distribution of the species, their ways of living, their hosts and their parasites. This is the first comprehensive work on the fauna of the GDR, since 1930 and makes it possible that not only specialists may do further work on this family.